2004
DOI: 10.1002/mawe.200400833
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Differentiation of Osteoblast‐Like Cells from Calvaria of Connexin43 Deficient Mice

Abstract: Extensive cell‐cell‐coupling via gap junctions has been suspected to play an essential role for osteoblast development. Here, osteoblast‐like cells (OBL) from connexin(Cx)43 knock out mice were used to explore the role of Cx43 for osteoblast differentiation. Primary cultures of OBL were derived from calvaria of homozygous (Cx43‐/‐) and heterozygous (Cx43+/–) knock out mice and also from wild type controls (Cx43+/+). In Cx43‐/‐ OBL Lucifer Yellow dye coupling was largely abolished demonstrating that small molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 42 publications
(45 reference statements)
1
5
2
Order By: Relevance
“…These findings support a previous study where no marked differences between the proliferation rates of wild-type and Cx43-null osteoblasts were observed (26). However, in a study using calvarial explants the cell outgrowth from Cx43-null tissue was significantly slower than the wild-type during the first week in culture but became markedly faster than in wild-type explants after the third week (49). The difference in findings between cell cultures (where differences in growth rate have not been detected) and explants (where variable growth that differs between genotype has been described) might simply be due to geometric constrains on growth in the explant conditions; alternatively a more complex phenomenon may be involved, such as a downstream effect of Cx43 ablation as the authors proposed (49).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These findings support a previous study where no marked differences between the proliferation rates of wild-type and Cx43-null osteoblasts were observed (26). However, in a study using calvarial explants the cell outgrowth from Cx43-null tissue was significantly slower than the wild-type during the first week in culture but became markedly faster than in wild-type explants after the third week (49). The difference in findings between cell cultures (where differences in growth rate have not been detected) and explants (where variable growth that differs between genotype has been described) might simply be due to geometric constrains on growth in the explant conditions; alternatively a more complex phenomenon may be involved, such as a downstream effect of Cx43 ablation as the authors proposed (49).…”
Section: Discussionsupporting
confidence: 91%
“…This pattern of delayed differentiation observed in our selected hTERT Cx43-null osteoblast lines is somewhat similar to that previously reported for Cx43-null calvarial osteoblasts (26), but it differs from the similar differentiation seen in calvarial osteoblasts derived from transgenic mice (Gja1 Jrt/ϩ ) expressing one of the dysfunctional Cx43 mutations causing ODDD (29). Our findings also contrast with those showing increased ALP expression in osteoblasts cultured from explants of Cx43-null calvaria (49). As mentioned above, the extent to which these results can be compared with those of cell lines may not be straightforward.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Other studies on this type of cells [13] and also on passaged cells [14] have revealed several alterations secondary to the loss of Cx43 such as a reduction of dye coupling strength, a lowered in vitro mineralization, changes in the expression of alkaline phosphatase, an over-expression of Cx45, and finally changes in growth and adhesion. These changes showed a clear gene dosage effect, i.e., were less pronounced in Cx43+/-than in Cx43-/-OBL [13,14], further suggesting a causal relationship between loss of Cx43 and the respective changes. The amplified [Ca 2+ ] i responses described here differ in this respect, as they were restricted to Cx43-/-OBL and were not found in wild type or heterozygous Cx43+/-animals.…”
Section: Discussionmentioning
confidence: 96%